Adaptabilidad de líneas promisorias y variedades de arroz (Oryza Sativa l.) en el sistema bajo riego para condiciones de bosque seco espinoso - Jaén y Bagua. - Salazar Cubas, Nelly (2003)
This research was carried out in the provinces of Utcubamba, Bagua and Jaen in the departments of Amazonas and Cajamarca respectively, with the main objective to determine the suitability 6 provisoras rice lines in 3 locations thorny dry forest for which it was used the randomized complete block design combined with analysis of variance, with the study materials promising lines 6 and 5 commercial varieties distributed in 3 blocks and 33 sub plots for each locality. the study material used in the research trial came from the experimental station huarangopampa, also one from commercial variety of rice federation of Colombia (Fedearroz). an average level of technology used in conducting the experiment. It performed the statistical analysis it was concluded that the t9 varieties (INIA bijao 501) and t1 or (Moor) recorded the highest averages for grain yield, while with respect to lines t3 (ir69595-9-kkl-44- bn-21-1-b) was the only line that scored an acceptable average.